Nyerere freedom and development - Nyerere, Julius K. (Dar es Salaam Oxford University Press, 1973)
Freedom and Development/Uhuru na Maendeleo, it is a representative sample of Tanzania's and her leader's views on such subjects as socialism, economic policy, human equality, African unity and liberation and international relations. However, president Nyerere emphasizes in the preface, that except where specifically mentioned these statements are not a description of what now exists in Tanzania or Africa, but rather of what is being aimed at. The book is a description of goals and of facts, and ideas of its author are intended as a contribution towards the achievement of those goals.
includes index
Keywords: Freedom, Development Socialism Politics